Political economy of deregulation: an impact analysis of Nigerian Telecommunications (2000-2014) - Moniruzzaman, Md. (Medwell Publishing, 2018)
Telecommunications remain one of the strategic economic sectors that assume prominence in the current discourses on the growth and integration of national economies and transnational production. Effective telecommunication system enables countries to achieve impressive socioeconomic gains. However, the Nigerian telecommunications under state monopoly was characterised by gross inefficiency, financial mismanagement and non-profitable. Consequently, the government has put a conscious strategy towards regulatory reforms in the sector. The reform emphasised on market opening by allowing entry for private and transnational operators into the country’s telecommunication market which eventually led to the transformation of the industry. Examining four factors, namely- teledensity, broadband penetration, revenue contribution to GDP and employment generation, this study finds that post-deregulation Nigerian telecommunication sector has shown evidence of efficiency and growth.